2015
DOI: 10.7763/ijcea.2015.v6.493
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Content of Bromine Compounds in the Product Oil of Pyrolysis Using Synthetic Hydrotalcite

Abstract: Abstract-Polystyrene plastic samples containing brominated flame-retardants (BR-PS) were pyrolyzed at 400 C using hydrotalcite to reduce the content of bromine compounds in the oil produced, in comparison with using sand, zeolite-4A, and zeolite-13X. The bromine plastic sample was prepared by mixing tetrabromobisphenol A and polystyrene, and added to a glass reactor, together with hydrotalcite, sand, zeolite-4A, or zeolite-13X. The product oil obtained by pyrolysis at 400 C from the BR-PS was mainly composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…It has also been reported in a study on the thermal degradation of ABS that the use of a half-batch reactor results in the enrichment of the contained brominated flame retardants into residual carbon [24]. We reported that HT addition in the pyrolysis of brominated plastics reduced the content of bromine compounds in the product oil [27]- [29]. The effect of HT addition with different elemental composition ratios in the pyrolysis of brominated polystyrene was also reported [30].…”
Section: Influence and Effect Of Pyrolysis With Additives In Tantalum...supporting
confidence: 61%
“…It has also been reported in a study on the thermal degradation of ABS that the use of a half-batch reactor results in the enrichment of the contained brominated flame retardants into residual carbon [24]. We reported that HT addition in the pyrolysis of brominated plastics reduced the content of bromine compounds in the product oil [27]- [29]. The effect of HT addition with different elemental composition ratios in the pyrolysis of brominated polystyrene was also reported [30].…”
Section: Influence and Effect Of Pyrolysis With Additives In Tantalum...supporting
confidence: 61%
“…Another study examined the thermal decomposition of tetrabromobisphenol A, a brominated flame retardant, in the presence of a zeolite catalyst (ZSM-5 or Y-type zeolite), whereby the latter catalyst was more effective in removing the bromine compound [27]. We previously reported that it was possible to reduce the content of bromine in the oil produced upon thermal decomposition of brominated polystyrene by using hydrotalcite (HT) additive [33]. HT is a layered double hydroxide consisting of a metal complex hydroxide comprising anionic species in the divalent Mg 2+ and trivalent Al 3+ host layers and interlayer of the guest layer [34], [35].…”
Section: Introductionmentioning
confidence: 99%
“…The yield of product oil was improved to 96% from 93% when the zeolite catalysts, H-USY or H-Beta, were used in a steam contact process for pyrolysis [27]. The content of the bromine compounds in the product oil was decreased by adding hydrotalcite (HT) in the pyrolysis of brominated plastic [28][29][30]. HT is composed of layers of hydroxides that can form a metal complex hydroxide, containing anionic hosts and Mg 2+ and Al 3+ interlamellar guests [31,32].…”
Section: Introductionmentioning
confidence: 95%